Type 2 Inflammation in Eosinophilic Esophagitis: From Pathophysiology to Therapeutic Targets - Racca, Francesca; Pellegatta, Gaia; Cataldo, Giuseppe; Vespa, Edoardo; Carlani, Elisa; Pelaia, Corrado; Paoletti, Giovanni; Messina, Maria Rita; Nappi, Emanuele; Canonica, Giorgio Walter; Repici, Alessandro; Heffler, Enrico (Frontiers in Physiology, 2022)
Eosinophilic esophagitis (EoE) is a chronic immune-mediated disease of the esophagus characterized clinically by symptoms related to esophageal dysfunction and histologically by eosinophil-predominant inflammation, whose incidence is rising. It significantly affects patients’ quality of life and, if left untreated, results in fibrotic complications. Although broad consensus has been achieved on first-line therapy, a subset of patients remains non-responder to standard therapy. The pathogenesis of EoE is multifactorial and results from the complex, still mostly undefined, interaction between genetics and intrinsic factors, environment, and antigenic stimuli. A deep understanding of the pathophysiology of this disease is pivotal for the development of new therapies. This review provides a comprehensive description of the pathophysiology of EoE, starting from major pathogenic mechanisms (genetics, type 2 inflammation, epithelial barrier dysfunction, gastroesophageal reflux, allergens, infections and microbiota) and subsequently focusing on the single protagonists of type 2 inflammation (involved cells, cytokines, soluble effectors, surface proteins and transcription factors) that could represent present and future therapeutic targets, while summarizing previous therapeutic approaches in literature.